MONITORING THE SITUATION EPIZOOTIC WORM INFESTATIONS OF THE GASTROINTESTINAL TRACT COWS IN UKRAINE: According veterinary statistics - Пономар, С. І.; Кручиненко, О. В. (Scientific Progress & Innovations, 2014)
The results of monitoring studies on epizootic situation in fasciolosis, paramfistomosis, dicroceliasis and strongyloidosis of the digestive system in Ukraine. The most disadvantaged areas in helminthiasis gastrointestinal tract are Volyn, Zhytomyr, Poltava, Rivne, Sumy and Chernihiv regions. During 2010-2011, 100 % of extensity of invasion by parasites paramfistomа registered in Donetsk region, dykrotseliyа - Volyn and stronhilyatа of the digestive system – in Rivne. During 2012-2013 he was 100 % of extensity of invasion dykrotseliya recorded in the Kiev region.